2013
DOI: 10.1038/gt.2013.65
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumor immunotherapeutic effect of B-cell-based vaccine transduced with modified adenoviral vector containing type 35 fiber structures

Abstract: For successful clinical tumor immunotherapy outcomes, strong immune responses against tumor antigens must be generated. Cell-based vaccines compromise one strategy with which to induce appropriate strong immune responses. Previously, we established a natural killer T-cell (NKT) ligand-loaded, adenoviral vector-transduced B-cell-based anticancer cellular vaccine. To enhance tumor antigen delivery to B cells, we established a modified adenoviral vector (Ad-k35) that encoded a truncated form of the breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Advances in cancer immunotherapy are not only changing standard therapies for cancer but are also expected to yield complete responses in patients with advanced cancer (25)(26)(27). Although various cancer immunotherapies, such as checkpoint inhibitors, immunostimulatory cytokines, tumor vaccines, and CAR-T cells, have shown clinical efficacy, a significant proportion of cancer patients still do not respond to any of these immunotherapies (28)(29)(30). Most immunotherapies have mainly focused on their effect on T cells, whereas NK cells are one of the most important effector arms, especially against MHC class I-deficient tumors, whose frequency is closely associated with the malignancy of the cancer (4,5,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in cancer immunotherapy are not only changing standard therapies for cancer but are also expected to yield complete responses in patients with advanced cancer (25)(26)(27). Although various cancer immunotherapies, such as checkpoint inhibitors, immunostimulatory cytokines, tumor vaccines, and CAR-T cells, have shown clinical efficacy, a significant proportion of cancer patients still do not respond to any of these immunotherapies (28)(29)(30). Most immunotherapies have mainly focused on their effect on T cells, whereas NK cells are one of the most important effector arms, especially against MHC class I-deficient tumors, whose frequency is closely associated with the malignancy of the cancer (4,5,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…centrifugation step at room temperature, and the cells were subsequently incubated for an additional 18 h (for the B/Mo/αGC preparation this step was skipped). αGC (KRN7000, Enzo Life Science, Japan) was loaded into the prepared B cells and monocytes for NKT activation based on our previous studies20212251.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we employed a B-cell-based antitumor vaccine (31,32). We have convincingly showed that a NKT ligand-loaded, B-cell-based vaccine elicits tumor-specific immune responses (21,33,34). We subcutaneously inoculated Balb/c mice with CT26 tumor cells on day 0 and then intraperitoneally injected the mice with 0.5 mg of antiosteopontin (MPIIIB10) or mIgG as a control every other day for 10 days (Fig.…”
Section: Antiosteopontin Enhances Antitumor Therapeutic Effect Of Celmentioning
confidence: 99%